Lacunas na evolução da via de reparo por excisão de nucleotídeos em eucariotos - Feltrin, Rayana dos Santos (2020)
Nucleotide excision repair (NER) is the most versatile DNA repair pathway as it removes different kinds of bulky lesions. Due to its essential role for genome integrity, it appeared early in the evolution of species. However, most published studies are focused on humans, mice, yeast or bacteria. Considering the large amount of information on genome databases, it is currently possible to retrieve sequences from NER components in many organisms. Therefore, we attempted to characterize the potential orthologs of 10 critical components of the human NER pathway in 12 eukaryotic species by using similarity and structural criteria through the use of bioinformatical tools. This approach has allowed us to characterize gene and protein structures comparatively, taking a glance at some evolutionary aspects of the NER pathway. We obtained significant search results for the majority of the proteins in most of the organisms studied, mainly for factors that play a pivotal role in the pathway. However, we revisited significant differences and found new aspects that may imply a distinct functioning of this pathway in different organisms. Through the demonstration of the heterogeneity of the gene structures and a variety in the protein architecture of the NER components evaluated, our results highlight important differences between human NER and evolutionarily distant eukaryotes.